ANALISIS PENGAMBILAN KEPUTUSAN EKONOMI RUMAHTANGGA PETANI KELAPA DI KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Amalia Putri; Syaiful Hadi; Djaimi Bakce (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
In general, the main  purpose of this research is to analyze the factors respect to the economic decision making of the household coconut farmers of production, the alocation of working time, income and the expenditure in Keritang, Indragiri Hilir. Approach to econometrics simultaneous equations by the method of Two Stage Least Square (2SLS) is used to answer the research purposes. The results showed: first, the production respect to unresponsive by the amount of productive coconut. Secondly, the alocation of working time on coconut farming respect to responsive by the income of coconut farming and the use of hired  labor. The use of hired  labor respect to responsive by the income of coconut farming. The alocation of non-working time of coconut farming respect to unresponsive by the income of non-working time of coconut farming. Thirdly, the income of non-coconut farming respect to unresponsif by the alocation of non-working time of coconut farming. Fourthly, non-food consumption respect to responsive by the household total income, food consumption, investment education and savings. Business  investment, expenditure leisure , and savings respect to responsive by household total income. Fifthly, An important government policy that is associated with an increased price and revitalization of coconut. The need for an increase in price over the pricing policy of coconut product or realize the strong bargaining position of farmers. Keywords: Household  Economic, Economic Decision